2021
DOI: 10.1007/s10668-021-01303-5
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based mapping and assessment of noise pollution in Safranbolu, Karabuk, Turkey

Abstract: In this study, it is aimed to determine and map the noise pollution levels in Safranbolu District Center, especially in the regions where motor vehicle and/or pedestrian traffic is intense. Forty-seven measurement points were selected for noise level measurements at the district center. Measurements were conducted at morning (8 a.m.–10 a.m.), lunchtime (12 p.m.–2 p.m.) and evening (6 p.m.–8 p.m.) hours of weekdays and weekends throughout the seasons of summer 2017 and winter 2018. The summer season weekdays no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Similarly, traffic noise index showed significantly different from late morning and evening time. Almost similar observation was reported by Esmeray et al [12].…”
Section: Field Measurement Acoustic Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, traffic noise index showed significantly different from late morning and evening time. Almost similar observation was reported by Esmeray et al [12].…”
Section: Field Measurement Acoustic Resultssupporting
confidence: 89%
“…S4). Traffic noise is a problem common to all developed and developing nations [12,40]. The graphical presentation of Noise Pollution level (NPL) and Traffic Noise Index (TNI) are as depicted and it is clear that noise pollution is the highest in the afternoon.…”
Section: Field Measurement Acoustic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GIS-based mapping has expanded in popularity in recent years, with applications in nearly every field and increased geographic data availability. GIS-based noise mapping is a useful technique for minimizing noise pollution, which could be hazardous to one's health in the current environment (Esmeray & Eren, 2021). It offers both numerically generated data and software created especially for environmental noise mapping applications.…”
Section: Gis-based Noise Mapmentioning
confidence: 99%
“…GIS databases represented the model's validated results, and the results serve as helpful maps for local government as a source of information in the decision-making process [21]. Bilaşco Ş et al [22] aimed to determine and map the levels of noise pollution in Safranbolu District Center, particularly in areas with high motor vehicle and pedestrian activity levels. The authors demonstrated that the overall quality of the acoustic environment in our research area was moderate, implying that long-term exposure to these levels can affect human health and quality of life.…”
Section: Environmental Modelling For Traffic Noise In Urban Areas Was Developed By Francismentioning
confidence: 99%